Inter-tube adhesion mediates a new pearling mechanism. Issue 1 (30th November 2015) - Yue, Tongtao; Tian, Falin; Sun, Mingbin; Zhang, Xianren; Huang, Fang
Abstract : A common mechanism for intracellular transport is the controlled shape transformation, also known as pearling, of membrane tubes. Abstract : A common mechanism for intracellular transport is the controlled shape transformation, also known as pearling, of membrane tubes. Exploring how tube pearling takes place is thus of quite importance to not only understand the bio-functions of tubes, but also promote their potential biomedical applications. While the pearling mechanism of one single tube is well understood, both the pathway and the mechanism of pearling of multiple tubes still remain unclear. Herein, by means of computer simulations we show that the tube pearling can be mediated by the inter-tube adhesion. By increasing the inter-tube adhesion strength, each tube undergoes a discontinuous transition from no pearling to thorough pearling. The discontinuous pearling transition is ascribed to the competitive variation between tube surface tension and the extent of inter-tube adhesion. Besides, the final pearling instability is also affected by tube diameter and inter-tube orientation. Thinner tubes undergo inter-tube lipid diffusion before completion of pearling. The early lipid diffusion reduces the extent of inter-tube adhesion and thus restrains the subsequent pearling. Therefore, only partial or no pearling can take place for two thinner tubes. For two perpendicular tubes, the pearling is also observed, but with different pathways and higher efficiency. The finite size effect is discussed by comparing the pearling of tubes with different lengths. It is expected that this work will not only provide new insights into the mechanism of membrane tube pearling, but also shed light on the potential applications in biomaterials science and nanomedicine.